Children's dreams : notes from the seminar given in 1936-1940 - Jung, C. G. (Carl Gustav), 1875-1961 (Jung, C. G. (Carl Gustav), 1875-1961. Philemon series., 2008)
In the 1930s C.G. Jung embarked upon a bold investigation into childhood dreams as remembered by adults to better understand their significance to the lives of the dreamers. Jung presented his findings in a four-year seminar series at the Swiss Federal Institute of Technology in Zurich. Children's Dreams marks their first publication in English, and fills a critical gap in Jung's collected works. Here we witness Jung the clinician more vividly than ever before--and he is witty, impatient, sometimes authoritarian, always wise and intellectually daring, but also a teacher who,